Panel Sequencing Identified a Novel Splice Site Mutation in Hermansky-Pudlak Syndrome Type 1 Patients - Boeckelmann, Doris; Sobotta, Felix; Andresen, Felicia; Szvetnik, Amina; Fels, Salome; Zieger, Barbara (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder. Patients with HPS characteristically present with oculocutaneous albinism, nystagmus and increased bleeding tendency. The symptoms are caused by malfunction of lysosome related organelles (i.e. melanosomes, platelets). Patients with HPS typically show impaired platelet delta granule secretion. We report three patients (two brothers and another unrelated patient) who presented with these typical symptoms. Methods and Results: Platelet aggregometry and flow cytometry analyses revealed pathological platelet function and decreased platelet delta granule secretion. Using NGS panel analysis comprising all 10 HPS genes a defect in the HPS1 gene was identified. The brothers share compound heterozygous a novel splice variant (c.987+1[G>A]) and an already reported mutation (c.1189[delC]). Although the third patient is not related with the brothers, he presented with the same one base pair deletion c.1189[delC] compound heterozygous with another already reported base pair deletion (c.355[delC]). Conclusions: Since HPS1 patients are at risk to develop pulmonary fibrosis at middle age, early genetic diagnosis of the HPS type is important for prognosis and treatment. In this study we identified a novel splice site variant (c.987+1[G>A]) in the HPS1 gene, diagnosed the patients as HPS1 type and therefore, enabled adequate follow-up and therapy.